PROFIL KEMAMPUAN REPRESENTASI MATEMATIS SISWA SEKOLAH DASAR DI KECAMATAN SUMEDANG UTARA - Hani Handayani; Rifahana Yoga Juanda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
Mathematical representation ability is the ability of students in issuing ideas and ideas in solving mathematical problems. The purpose of this study is to determine the profile of mathematical representation ability of elementary school students in North Sumedang District. The research method used is survey method. The survey method aims to collect data from a number of units or individuals at the same time. The research subjects were elementary school students with a total of 145 students who were students from six elementary schools in North Sumedang District. The data collected in this study was obtained from a test of mathematical representation ability in solving mathematical problems in elementary schools. The questions made are in accordance with mathematical representation indicators. Based on the results of data analysis from 145 students, students' verbal representation abilities reached 30.3% with very low categories, the ability of students' symbolic representation reached 25.2% with very low categories, and students' visual representation abilities reached 19.3% with very low. Overall students' mathematical representation ability reaches 24.9% in the very low category. From the results of data analysis it can be concluded that the mathematical representation ability of elementary school students in North Sumedang District is still very low.